Venturas y desventuras del enfoque del marco lógico - Sainz Ollero, Héctor (Revista Española de Desarrollo y Cooperación, 2023)
The articles tries to do an initial appraisal, based on the author’s personal experiences about the application of the Logical Framework Approach in the Spanish Cooperation, pointing out some usual flaws, and commenting some of the main criticisms about the validity of this framework. Finally, it poses a number of basic reflections before bringing an opinion related to the strengths and weaknesses of LFA.